Pengaruh Kecerdasan Emosional, Ketahanan Mental, dan Pengalaman Kewirausahaan Sebelumnya Terhadap Niat Berwirausaha: Studi Kasus pada Mahasiswa Anggota HIPMI PT UNDIP, UNNES, UDINUS - Purnama Julianti Lumban Batu; Wijang Sakitri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is motivated by the high level of educated unemployment and the suboptimal entrepreneurial intentions of students despite their involvement in entrepreneurial organizations such as HIPMI PT. The study aims to analyze the influence of emotional intelligence, mental resilience, and previous entrepreneurial experience on the entrepreneurial intentions of student members of HIPMI PT at Diponegoro University, Semarang State University, and Dian Nuswantoro University based on the Theory of Planned Behavior. This study uses a quantitative approach with a causal associative design. The research sample consisted of 159 students selected using purposive sampling technique from a population of 263 HIPMI PT members. Data were analyzed using multiple linear regression. The results showed that emotional intelligence and mental resilience had a positive and significant effect on entrepreneurial intentions, while previous entrepreneurial experience had a positive but insignificant effect. Simultaneously, all three variables had a significant effect on entrepreneurial intentions with a coefficient of determination of 37.9%. These findings indicate that psychological factors, especially emotional intelligence and mental resilience, have an important role in increasing students' entrepreneurial intentions.